2017
DOI: 10.1111/jcpe.12672
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition, dental caries and periodontal disease: a narrative review

Abstract: Aim To provide a narrative review of the role of macro‐ and micronutrients in relation to dental caries, gingival bleeding and destructive periodontal disease. Materials & Methods This review is based on systematic reviews (when available) and comparative human studies. Results Dental caries cannot develop without the presence of dietary fermentable carbohydrates, in particular sugar. The susceptibility to develop caries in the presence of carbohydrates may be influenced by genetics and micronutrients such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
142
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(153 citation statements)
references
References 45 publications
(58 reference statements)
2
142
0
9
Order By: Relevance
“…Although there was not a statistically significant association between lesion depth and patient risk, it is interesting to note that persons at elevated risk had a high percentage of their lesions into dentin (67%; n=204), with small percentages of their SOCLs with no caries (3%; n=8), inactive caries (5%; n=16), or into the enamel only (25%; n=77). These findings are consistent with other studies that have shown that patients in elevated-risk categories are at greater risk for future caries and this is an important factor to consider when developing a treatment plan 3233 . Our results suggest that patient risk influenced decisions to open lesions, as elevated-risk prevalence was higher among opened lesions (52%; n=305) than in the overall sample (35%; n=554).…”
Section: Discussionsupporting
confidence: 92%
“…Although there was not a statistically significant association between lesion depth and patient risk, it is interesting to note that persons at elevated risk had a high percentage of their lesions into dentin (67%; n=204), with small percentages of their SOCLs with no caries (3%; n=8), inactive caries (5%; n=16), or into the enamel only (25%; n=77). These findings are consistent with other studies that have shown that patients in elevated-risk categories are at greater risk for future caries and this is an important factor to consider when developing a treatment plan 3233 . Our results suggest that patient risk influenced decisions to open lesions, as elevated-risk prevalence was higher among opened lesions (52%; n=305) than in the overall sample (35%; n=554).…”
Section: Discussionsupporting
confidence: 92%
“…Given prior reports of the ineffectiveness of vitamin D in caries prevention, among girls after the age of 13 due to the influence of fat on the effectiveness of a fat‐soluble vitamin like vitamin D, we expected the association between vitamin D and caries experience to differ by gender but this was not the case. Furthermore, our findings suggesting that deficient levels (<30 nmol/L) of vitamin D may pose a greater concern for caries experience than inadequate (30‐<50 nmol/L) levels, should be taken with caution given these associations were modest and imprecisely estimated.…”
Section: Discussionmentioning
confidence: 99%
“…18 Hypoplastic enamel promotes adherence and colonization of the tooth surface by cariogenic bacteria. 19 It has been suggested that caries susceptibility even after tooth eruption may be influenced by micronutrients like vitamin D. 20 Several studies have previously reported inverse associations between serum vitamin D levels and childhood caries, [21][22][23] and systematic reviews of controlled clinical trials found probable evidence for supplemental vitamin D use among children on lower dental caries occurrence. 24,25 However, none have specifically investigated serum vitamin D concentrations and dental caries experience among adolescents.…”
mentioning
confidence: 99%
“…It is substantially, but not entirely, based upon one systematic review of the available and published evidence relating to genetic risk factors for periodontal diseases and caries (Nibali et al 2017), one narrative review on the role of diet and nutrition in development and progression of periodontal diseases and caries (Hujoel & Lingstrom 2017), and reference documentation provided on common modifiable risk factors common to both disease groups. Evidence for the role of genetic factors in periodontal diseases initially emerged from familial aggregation studies (Saxen 1980, van der Velden et al 1993 and from studies of twins reared together and apart (Michalowicz et al 1991).…”
Section: Inherited and Acquired Risk Factors For Dental Caries And Pementioning
confidence: 99%